Bax expression and apoptotic cell death in Fanconi anaemia peripheral blood lymphocytes - Baruque, G. A. (Cell Prolif, 2007)
Abstract.  Objective: Deregulated apoptosis might be involved in some of the features of Fanconi anaemia (FA). The possibility that the pro‐apoptotic Bax protein could be involved in an increased susceptibility to apoptosis in FA patients was investigated. Materials and methods: Intracellular Bax expression, Bcl‐2 expression (an anti‐apoptotic protein) and cell death were analysed in 26 FA peripheral blood lymphocyte samples. Results: Most FA samples (69%) displayed increased levels of Bax and were more susceptible to both spontaneous apoptosis and mitogen activation‐induced cell death. Two subgroups were identified: one presented elevated levels of Bax (n = 18), whereas the other (n = 8), had Bax levels lower than controls. Two subgroups based on Bcl‐2 expression were also identified: one with normal and another with high Bcl‐2 expression. No inverse correlation was found between Bcl‐2 levels and Bax expression. A clear difference in susceptibility to induced cell death could be observed between control and FA samples. The best correlation was observed between high levels of Bax and mitogen‐induced apoptosis of cells; these displayed characteristics of necrosis secondary to apoptosis, suggesting that the intrinsic apoptotic pathway was being activated. Conclusion: Despite increased susceptibility to cell death induction, there was no correlation between Bax levels, chromosome breakage, haematological parameters or androgen therapy. The importance of apoptosis and Bax expression in the clinical development of FA awaits clarification.